ECONOMY "SMART BUILDINGS" HOUSING - Đurić, Stanka (Journal of process management and new technologies, 2016)
Expensive imported energy products (liquid fuels and gas) and the need for energy independence, direct us towards a strategy of increased use of renewable energy sources. Energy independence of one country can be read in the percentage of renewable energy sources (geothermal water, wind, water, hydropower, biomass, solar energy), compared to the amount of energy that is imported (liquid fuels and gas). In developed European countries, renewable energy sources make up 10 - 12% of the total energy balance, with us - just 1%. Environmental awareness obliges us to think about living in harmony with nature, using technologies that do not threaten the planet. If you would like to save a life on earth, must change the way of life and the way of construction. Inadequate access to jobs, is one of the most important contributions to global warming of the planet. Neanderthal Man is an intuitive built in harmony with nature. Technical and technological advances of civilization has brought the design and construction of the exhaust of fossil fuels, accumulate un-recyclable materials, improve emissions and alienate man from nature. For designers and investors is to develop, design and build "green".